Bidirectional synaptic structural plasticity after chronic cocaine administration occurs through Rap1 small GTPase signaling - Cahill, Michael E. (Neuron, 2016)
Dendritic spines are the sites of most excitatory synapses in the CNS, and opposing alterations in the synaptic structure of medium spiny neurons (MSNs) of the nucleus accumbens, a primary brain reward region, are seen at early vs. late time points after cocaine administration. Here we investigate the time-dependent molecular and biochemical processes that regulate this bidirectional synaptic structural plasticity of NAc MSNs and associated changes in cocaine reward in response to chronic cocaine exposure. Our findings reveal key roles for the bidirectional synaptic expression of the Rap1b small GTPase and an associated local-synaptic protein translation network in this process. The transcriptional mechanisms and pathway-specific inputs to NAc that regulate Rap1b expression are also characterized. Collectively, these findings provide a precise mechanism by which nuclear to synaptic interactions induce “metaplasticity” in NAc MSNs, and we reveal the specific effects of this plasticity on reward behavior in a brain circuit-specific manner.